Analysis of the national conditions for the development of entrepreneurship in Cuba - Martínez Gil, Lisbet (2021)
Entrepreneurship acquires regional and global relevance, as a component of economic systems and national development policies. The study and research on the subject in Cuba is still considered scarce. This work aims to analyze the national conditions for entrepreneurship in this country. Based on the Global Entrepreneurship Monitor (GEM) model, an electronic survey was conducted among Cuban academics, researchers, and entrepreneurs, who rated different conditions necessary for the development of entrepreneurial activity. References from previous research are also taken. The current state of the framework of conditions necessary for entrepreneurship in Cuba does not favor the growth and contribution of this activity to Cuban economic and social development.